2021
DOI: 10.1038/s41467-020-20656-5
|View full text |Cite
|
Sign up to set email alerts
|

Contextual dependencies expand the re-usability of genetic inverters

Abstract: The implementation of Boolean logic circuits in cells have become a very active field within synthetic biology. Although these are mostly focussed on the genetic components alone, the context in which the circuit performs is crucial for its outcome. We characterise 20 genetic NOT logic gates in up to 7 bacterial-based contexts each, to generate 135 different functions. The contexts we focus on are combinations of four plasmid backbones and three hosts, two Escherichia coli and one Pseudomonas putida strains. E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 54 publications
(80 reference statements)
0
30
0
Order By: Relevance
“…In summary, these results confirmed that the characterisation of individual gene-fusions differ in relation to enzyme function and the state of protein folding within the cell. This is a form of context dependency, which is an increasingly important factor in the design of genetic circuits and pathways in synthetic biology [ 23 ]. Next, with this new knowledge, we set upon refactoring the pathway to optimise raspberry ketone production.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, these results confirmed that the characterisation of individual gene-fusions differ in relation to enzyme function and the state of protein folding within the cell. This is a form of context dependency, which is an increasingly important factor in the design of genetic circuits and pathways in synthetic biology [ 23 ]. Next, with this new knowledge, we set upon refactoring the pathway to optimise raspberry ketone production.…”
Section: Resultsmentioning
confidence: 99%
“…Will they keep their function over evolutionary timescales, which are quite short in cellular populations? Ecological robustness and evolutionary stability should be part of the design of genetic circuits ( Cardinale and Arkin, 2012 ; Tas et al, 2021 ). Likewise, efforts to ‘edit’ the microbiome in situ should contemplate the ecological and evolutionary response of the community to those genetic changes ( Brenner et al, 2009 ; Chang et al, 2021 ; Goldman and Brown, 2009 ; McCarty and Ledesma-Amaro, 2019 ).…”
Section: Does It Matter?mentioning
confidence: 99%
“…In addition, the high quality of i NL638, in terms of consistency and interoperability, paves the way for the future multistrain modeling of the H. influenzae species using the strain RdKW20 as a reference. As shown by the strain-dependent effect of the inhibitor tested, the impact of metabolic context is gaining relevance as a key factor driving cell behavior ( 67 ). Therefore, further H. influenzae multistrain modeling effort could lead to the identification of secondary metabolic hubs modulating the response of known and novel drugs, promoting the establishment of synergistic and more robust antibacterial treatments.…”
Section: Discussionmentioning
confidence: 99%